Fracture behaviour of fibre reinforced composites containing circular hole - Srivastava, V. K. (Journal of Structural Engineering, 2025)
The objective of present work is to explain the fracture behavior of fiber reinforced composites containing holes and construct an efficient and reliable model, which can be used for prediction of notched strength of various laminates containing circular holes. The Sequential Fiber Failure Criterion and Average Stress Criterion are proposed, which can be used for the prediction of notched strength of fiber reinforced composite laminates containing holes subjected to tensile load at infinity. In this work the variation of notched strength with specimen width is also studied with the help of experiments and a model is constructed to obtain the notched strength of a specimen having different width from tested coupons.